1995
DOI: 10.1128/jvi.69.12.8137-8141.1995
|View full text |Cite
|
Sign up to set email alerts
|

Molecular linkage of hantavirus pulmonary syndrome to the white-footed mouse, Peromyscus leucopus: genetic characterization of the M genome of New York virus

Abstract: The complete M segment sequences of hantaviruses amplified from tissues of a patient with hantavirus pulmonary syndrome in the northeastern United States and from white-footed mice, Peromyscus leucopus, from New York were 99% identical and differed from those of Four Corners virus by 23%. The serum of this patient failed to recognize a conserved, immunodominant epitope of the Four Corners virus G1 glycoprotein. Collectively, these findings indicate that P. leucopus harbors a genetically and antigenically disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(40 citation statements)
references
References 37 publications
3
35
0
2
Order By: Relevance
“…The two sequences were 98.2% identical within the region studied. A similar level of identity (99%) has been reported for the complete M sequences determined with specimens from a hantavirus pulmonary syndrome (HPS) patient and a wild-type New York hantavirus from a white-footed mouse in the northeastern United States (19). Nichol et al (28) have reported 99 to 100% identity between partial Msegment sequences of Sin Nombre hantavirus (SN) derived from three HPS patients and those derived from deer mice trapped at or near the patients' residences in the Four Corners region of the southwestern United States.…”
Section: Discussionsupporting
confidence: 66%
“…The two sequences were 98.2% identical within the region studied. A similar level of identity (99%) has been reported for the complete M sequences determined with specimens from a hantavirus pulmonary syndrome (HPS) patient and a wild-type New York hantavirus from a white-footed mouse in the northeastern United States (19). Nichol et al (28) have reported 99 to 100% identity between partial Msegment sequences of Sin Nombre hantavirus (SN) derived from three HPS patients and those derived from deer mice trapped at or near the patients' residences in the Four Corners region of the southwestern United States.…”
Section: Discussionsupporting
confidence: 66%
“…[2][3][4][5][6][7][8] Seven members of the virus family Bunyaviridae, genus Hantavirus are known to cause HPS: Andes virus (ANDV), Bayou virus (BAYV), Black Creek Canal virus (BCCV), Choclo virus (CHOV), Laguna Negra virus (LANV), New York virus (NYV), and Sin Nombre virus (SNV). 3,5,6,[9][10][11][12] None of the 9 other hantaviruses native to the Americas, including Maporal virus (MAPV), has been associated with HPS or any other human disease. [13][14][15] Specific members of the rodent family Cricetidae are the principal hosts of the hantaviruses known to cause HPS.…”
Section: Introductionmentioning
confidence: 99%
“…P. leucopus have been used for studies of social interactions and stress physiology (Southwick 1964), as well as for the investigation of photoperiodism and the action of melatonin on the regulation of hormone secretion and reproductive physiology (Glass & Lynch 1982;Glass & Knotts 1987;Glass & Dolan 1988;Weaver et al 1990). These animals came to public attention as the primary reservoir host for Borrelia burgdorferi sensu stricto, the aetiological agent of lyme disease (Magnarelli et al 1988(Magnarelli et al , 1994Hofmeister & Childs 1995;Hofmeister et al 1999), and they may also be hosts for species of hantavirus (Hjelle et al 1995;Lyubsky et al 1996;Morzunov et al 1998). More recent studies have focused on behavioural and reproductive physiology of P. leucopus mice using different breeding practices under long-term captivity, with data showing that adaptation can be rapid, affecting reproductive patterns and behaviour, even under breeding protocols designed to minimize the rate of genetic change due to random drift and inadvertent selection (Malo et al 2010;Lacy et al 2013).…”
mentioning
confidence: 99%